2022
DOI: 10.1070/qel18046
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of an array of single-electron quantum dots with a microcavity field with allowance for Coulomb correlations

Abstract: We consider an ordered array of semiconductor singleelectron quantum dots located in the antinode of a mode of a microcavity based on a two-dimensional photonic crystal. The influence of Coulomb effects on the energy exchange between quantum dots and the mode is studied in arrays for different numbers of dots. The stability of resonant electron – photon dynamics is analysed as a function of technological deviations of the dot parameters caused by the imperfection of the manufacturing procedure. Using the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…By alternating the QDs with the p x -and p y -orbitals, one can significantly weaken the Förster energy transfer between the QDs and neglect the non-diagonal components of the Hamiltonian equation ( 4). The results obtained earlier for the linear sensor structure indicate a monotonic decrease in contrast with a growth of N associated with a gradual decrease in the influence of the electrons in the measured QDs on the remote QDs in the chain, and hence on photon transport through the MR [17]. A consequence of this is the restoration of the polariton Tavis-Cummings spectrum.…”
Section: Effect Of Ring Array Parameters and Measured Qd Position On ...mentioning
confidence: 74%
See 4 more Smart Citations
“…By alternating the QDs with the p x -and p y -orbitals, one can significantly weaken the Förster energy transfer between the QDs and neglect the non-diagonal components of the Hamiltonian equation ( 4). The results obtained earlier for the linear sensor structure indicate a monotonic decrease in contrast with a growth of N associated with a gradual decrease in the influence of the electrons in the measured QDs on the remote QDs in the chain, and hence on photon transport through the MR [17]. A consequence of this is the restoration of the polariton Tavis-Cummings spectrum.…”
Section: Effect Of Ring Array Parameters and Measured Qd Position On ...mentioning
confidence: 74%
“…The fundamental modes have a much lower quality factor compared to WGMs so their use is possible when developing devices that do not require a high quality factor of MRs. In [17], a procedure for detecting an electron located in a QD using a linear array of QDs placed in a defective region of a photonic crystal was proposed. It was shown that for the effective operation of the detector it is necessary that the Rabi frequency of the energy exchange between each QD in the array and the defect mode be the same.…”
Section: Optical Microdisk Modes and Their Coupling To The Qd Ring Arraymentioning
confidence: 99%
See 3 more Smart Citations